Unequal access to scientific knowledge - Tilly, Charles (Tempo Social, 2006)
The author raises questions about unequal access to scientific knowledge whose consequences affect human well being: control over production of that knowledge, control over its distribution, and access to that knowledge by people whose well being it will or could affect. I will try to show how and why they matter. the problem of access to scientific knowledge involves agency, identity, and freedom. It involves those themes in three different ways. First, the production and distribution of scientific knowledge depends on knowledgeable agents who almost inevitably hoard their knowledge to the differential advantage of themselves and their sponsors. Second, control over scientific knowledge organizes around identity-defining boundaries between those who have rights to that knowledge and those who lack such rights. Third, overcoming the barriers between beneficiaries and victims of unequal access ordinarily requires heroic agency on the part of advocates and political authorities.